Induction of the Stringent Response Underlies the Antimicrobial Action of Aliphatic Isothiocyanates - Nowicki, Dariusz; Krause, Klaudyna; Szamborska, Patrycja; Żukowska, Adrianna; Cech, Grzegorz M.; Szalewska-Pałasz, Agnieszka (Frontiers in Microbiology, 2021)
Bacterial resistance to known antibiotics comprises a serious threat to public health. Propagation of multidrug-resistant pathogenic strains is a reason for undertaking a search for new therapeutic strategies, based on newly developed chemical compounds and the agents present in nature. Moreover, antibiotic treatment of infections caused by enterotoxin toxin-bearing strain—enterohemorrhagic Escherichia coli (EHEC) is considered hazardous and controversial due to the possibility of induction of bacteriophage-encoded toxin production by the antibiotic-mediated stress. The important source of potentially beneficial compounds are secondary plant metabolites, isothiocyanates (ITC), and phytoncides from the Brassicaceae family. We reported previously that sulforaphane and phenethyl isothiocyanate, already known for their chemopreventive and anticancer features, exhibit significant antibacterial effects against various pathogenic bacteria. The mechanism of their action is based on the induction of the stringent response and accumulation of its alarmones, the guanosine penta- and tetraphosphate. In this process, the amino acid starvation path is employed via the RelA protein, however, the precise mechanism of amino acid limitation in the presence of ITCs is yet unknown. In this work, we asked whether ITCs could act synergistically with each other to increase the antibacterial effect. A set of aliphatic ITCs, such as iberin, iberverin, alyssin, erucin, sulforaphen, erysolin, and cheirolin was tested in combination with sulforaphane against E. coli. Our experiments show that all tested ITCs exhibit strong antimicrobial effect individually, and this effect involves the stringent response caused by induction of the amino acid starvation. Interestingly, excess of specific amino acids reversed the antimicrobial effects of ITCs, where the common amino acid for all tested compounds was glycine. The synergistic action observed for iberin, iberverin, and alyssin also led to accumulation of (p)ppGpp, and the minimal inhibitory concentration necessary for the antibacterial effect was four- to eightfold lower than for individual ITCs. Moreover, the unique mode of ITC action is responsible for inhibition of prophage induction and toxin production, in addition to growth inhibition of EHEC strains. Thus, the antimicrobial effect of plant secondary metabolites by the stringent response induction could be employed in potential therapeutic strategies.